Sarjakuva translatorisen toiminnan välineenä - Pitkäsalo, Eliisa; Haavisto, Vaula; Kalliomaa-Puha, Laura (Suomen kääntäjien ja tulkkien liitto – Finlands översättar- och tolkförbund ry, 2025)
This article examines two types of translatorial action: translating social welfare documents into comics and using these comics as tools in interactions between social workers and clients. The translation process involves careful selection of visual and verbal elements to ensure that essential information is not lost or oversimplified. Visual translation strategies must consider clarity and the emotional impact of images. Comics can make implicit information explicit, enhancing understanding and engagement. Research data suggest that comics can also support interaction, with social workers acting as paraprofessional translators. Comics aid in explaining services and rules, supporting workers’ paraprofessional translatorial work as well as both worker and client memory. This dual-level translatorial action—creating and using comics—enhances client participation and strengthens the role of social workers as communicators.